TERMS OF THE CONTRACT IN THE VALIDITY OF MUAMALAT - Wulan Dayu (Proceeding International Seminar of Islamic Studies, 2023)
Contract arrangements are an important aspect of the validity of muamalat, especially in the context of sharia law. A contract is an agreement between two mutually binding parties to perform an action or provide an item or service. In the context of muamalat, a contract is an agreement between parties who wish to carry out a transaction that is lawful and in accordance with sharia principles, covering several aspects, including an agreement between the two parties, the object of the transaction that is lawful and in accordance with sharia principles, and other provisions in accordance with sharia law. In this case, the parties must understand and agree on the contents of the contract clearly and in detail, so that disputes do not occur in the future. Besides that, Contract arrangements in the validity of muamalat must also pay attention to the applicable muamalah principles, such as fairness, openness and equality. The contract made must be fair for both parties, not detrimental to either party, and does not violate sharia principles. If there is a dispute or disagreement between the two parties regarding the contents of the contract, the settlement must be carried out in ways that are in accordance with sharia law, such as through a process of deliberation or arbitration. In conclusion, the arrangement of contracts in the validity of muamalat is very important to ensure that the transactions carried out are in accordance with sharia principles and do not violate sharia law.